2011
DOI: 10.1017/s1368980011002576
|View full text |Cite
|
Sign up to set email alerts
|

Wholegrain cereals and bread: a duet of the Mediterranean diet for the prevention of chronic diseases

Abstract: Objective: The promotion of healthy lifestyles is one of the major goals of governments and international agencies all over the world. Wholegrain cereals are rich in nutrients and many phytochemical compounds, with recognised benefits for health, including dietary fibre, a number of phenolic compounds, lignans, vitamins and minerals and other bioactive components. The aim of the present work is to review the fundamental studies that support the consumption of wholegrain cereals and bread to prevent chronic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 58 publications
1
94
0
2
Order By: Relevance
“…However, these relationships have been mainly observed for whole-grain bread or cereals (Gil et al 2011), whereas the associations for white bread are not clear, and have been associated with increased adiposity and weight gain (Bautista-Castano et al 2012a;Bautista-Castano and Serra-Majem 2012b;Williams 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, these relationships have been mainly observed for whole-grain bread or cereals (Gil et al 2011), whereas the associations for white bread are not clear, and have been associated with increased adiposity and weight gain (Bautista-Castano et al 2012a;Bautista-Castano and Serra-Majem 2012b;Williams 2012).…”
Section: Introductionmentioning
confidence: 99%
“…gluten quality) and did not give much consideration to the nutritional and nutraceutical importance of wheat consumption in the human diet (Peccetti and Annicchiarico, 1998;Motzo et al, 2004). Recently, Fardet (2010) provided a complete description of the bioactive compounds present in whole wheat grains (including dietary fibre, polyphenols and carotenoids) and Gil et al (2011) reported on the numerous studies that have demonstrated a direct relationship between wholegrain consumption and prevention of chronic diseases (i.e. diabetes, colon cancer).…”
Section: Introductionmentioning
confidence: 99%
“…Cereal-based foods, whole grain in particular, including bread, have a vital role in maintaining health and well-being. Studies consistently indicate that the regular consumption of whole grain cereals helps to reduce the risk of cardiovascular diseases, type 2 diabetes mellitus, certain types of cancer and several gastrointestinal pathologies (Gil et al, 2011). Despite the recommendatory intake of three servings per day of whole-grain products, it was shown worldwide that children and adolescents consume only about one serving of whole-grain products daily (Burgess-Champoux, 2006; Thane et al, 2005;Vereecken et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding author E-mail: gretak@fthm.hr Whole grain cereals are of special importance within this dietary pattern due to their numerous nutrients and phytochemicals such as dietary fibre, antioxidants including phenolic compounds, phytoestrogens including lignans, vitamins and minerals (Gil et al, 2011). Over the past few decades, there has been a gradual shift away from this dietary pattern by the inhabitants of the Mediterranean basin, especially the young generations.…”
mentioning
confidence: 99%